Sull'idronimo Dragonja/Dragogna - Furlan, Metka (Linguistica (Ljubljana), 2015)
Although the name of the river Dragonja was as Argaone (...) first mentioned by Anonymus from Ravenna already in the 7th century, the modern hydronymic forms Slovene Draginja, Croatian Dragonja and Italian Dragogna, are only indirectly connected with it. After the substratal hydronym was first, most likely as Argaone, borrowed from the Roman spoken Istrian population and after the 10th century underwent the Istro-Venetian phonetic change into *Argone (the type taola > tola), it was transonimizated and used also as the name of Piranian gulf (Largom, Largone, Largon, Laron). The homonymy *Argone 'the river Dragonja; the Piranian gulf' caused that the phrase *fiume d'Argone *'the river of Argone = Piranian gulf' began to be used for naming the river Dragonja, which via agglutination brought about the form *Dargone. Because the river Dragonja often flooded during heavy rainfall, the hydronymic form *Dargone was associated by the people in the area of the river Dragonja with dragons as actors of the devastating floods. The linguistic sign of this perception was at first the metathesis *Dargone --- *Dragone, influenced by Italian dragone 'dragon' and later the morphological modification of *Dragone into Dragogna *'the area (= river) of dragons' (the type vigna 'vineyard' < *'the area of vines'). The Slovene and Croatian hydronymic form Dragonja is therefore a young borrowing from Istro-Ventian Dragogna. The previous interpretation by Ramovš that the Slovene-Croatian hydronym Dragonja is of substratal origin and reflects the Slavic metathesis of liquids is nowadays unacceptable because such a form would result in Slovene-Croatian **Dragin or **Draginja.
Keywords: Dragonja (reka); etimologija; étymologie; etymology; geografska imena; hydronymes; Istra; Istria; Istrie; Slovene; slovenščina; toponymes; vodna imena